Schoolgirls' health agency: silence, upset and cooperation in a psycho-educational assemblage. (4th June 2018) - Wickström, Anette
ABSTRACT: Purpose: Since the millennium, manual-based preventive health programmes, drawing on psychological models of behaviour management, have dominated psycho-educational practices in school. The aim of this article is to study the health agency of 13-year-old schoolgirls participating in a programme for improving schoolchildren's psychological health in Sweden. Method: Drawing on Deleuze and Guattari's theories of assemblages, the interaction between schoolchildren, teachers, the manual and psycho-educational techniques is scrutinized. The methodology of assemblage ethnography is used in the analysis of video observations of 13 course meetings. Results: Three salient attitudes in relation to the possibilities built up for the schoolgirls are identified— silence, upset and cooperation . The girls' acts and stories question the psycho-centric, individualized and gender-normative approach used in psycho-educational programmes and make visible the relational and contextual aspects of schoolchildren's psychological health. Conclusion: Children depend on multiple factors for their agency; the institutional networks they are involved in both allow and restrict their actions. The study demonstrates that focusing on children as health actors, in the sense that agency develops in the assemblages children take part in, can complement the knowledge base and question the predominant framing of psychological health.